2018
DOI: 10.15406/ijh.2018.02.00057
|View full text |Cite
|
Sign up to set email alerts
|

Investigating regional groundwater flow systems in baja california central desert region

Abstract: In Northern Baja California, environmental conservation may not be fully accomplished in the absence of a clear understanding of key factors controlling and protecting biodiversity. Groundwater is an environmental agent triggering the presence of a wide range of arid ecosystems; therefore, any sustainable development in the region has to maintain a balance between environmental, social and economical benefits. The present study has placed a great emphasis on the understanding and distribution of groundwater fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
1
2
1
1
Order By: Relevance
“…The high pH, Na concentration and alkalinity of WC1 indicate high CO 2 inputs and hydrolysis of Na-rich silicates. Similar compositions were reported for groundwater in Baja California, which had undergone deep but rapid flow through fractured igneous and metamorphic rocks [50]. However, the high TDS of WC1 suggests a long residence time or higher weathering rates, possibly influenced by elevated temperatures.…”
Section: Chemical Constraints On Solute Fluxessupporting
confidence: 66%
“…The high pH, Na concentration and alkalinity of WC1 indicate high CO 2 inputs and hydrolysis of Na-rich silicates. Similar compositions were reported for groundwater in Baja California, which had undergone deep but rapid flow through fractured igneous and metamorphic rocks [50]. However, the high TDS of WC1 suggests a long residence time or higher weathering rates, possibly influenced by elevated temperatures.…”
Section: Chemical Constraints On Solute Fluxessupporting
confidence: 66%
“…Down‐canyon, the spring waters were associated slightly more with Na–K–Cl type waters, suggesting moderate dissolution of the rhyolitic aquifer material (Figure 3B). Major ion compositions of samples in this study showed less fluid‐rock interaction than regional groundwaters published by Ouysse et al (2018). The ranges found for Ca/Na (0.8 to 2.4) and Alkalinity/Na (1.5 to 4.2) correspond to silicate weathering with Ca/Na relatively larger values compared with the one found in large rivers (0.3 to 1) but well below the typical range for carbonate weathering (20 to 80) (Gaillardet et al 1999).…”
Section: Resultscontrasting
confidence: 50%
“…These values are consistent with the conclusion of Eastoe et al (2015) that recharge to groundwater systems is primarily from tropical storms. δ 18 O and δ 2 H isotopes of spring water collected in this study were representative of the range of the regional shallow groundwaters (Wassenar et al 2009;Kretzschmar and Frommen 2013;Birkle et al 2016;Tamez-Meléndez et al 2016;Ouysse et al 2018).…”
Section: Water Stable Isotopesmentioning
confidence: 78%
“…Los complejos procesos que actúan sobre múltiples escalas espaciales y temporales complican el nivel de acción; la cuenca hidrológica debe ser la base para entender la función adecuada de los sistemas de flujo y los procesos, así como para la correcta planificación y gestión del agua y el territorio (Carrillo-Rivera y Cardona, 2008;Ouysse et al, 2018;Yu y Duffy, 2018).…”
Section: Introductionunclassified